Building Brand Awareness of Fusion Restaurant Business in Narathiwat Province - Benharoon, S. Y.; Mudor, Hamdia (Journal of International Studies, Prince of Songkla University, 2024)
Building brand awareness is trustworthy and memorable among consumers; it is of the utmost importance for today’s service organizations. This qualitative research aimed (1) to analyze brand identity, and (2) to investigate communication methods, and strategies used to build up brand awareness for the fusion restaurant business in Narathiwat province. Data collection tool was in-depth interviews with entrepreneurs and employees of five fusion restaurants, consisting of two to three people each, totaling 11 informants, using a purposive sampling method. Additionally, the researchers analyzed messages conveyed through logos, images, slogans, and brand graphics of the case studies. The research results showed that the brand identity of the fusion restaurants can be divided into five categories: (1) Gallery cafe’ & bistro; (2) Authentic Italian homemade pizza; (3) Halal Korean food; (4) Healthy food, and (5) Contemporary Thai food. Those restaurants in research studies have similar methods of building brand awareness. They used social media as the main channel, and created great content to attract consumers via integrated online/offline advertising and public relations. They also employed influencers to promote and review products, as well as special promotions and discounts, using a viral marketing strategy.